Titanium Nanotube Modified With Silver Cross-Linked Basic Fibroblast Growth Factor Improves Osteoblastic Activities of Dental Pulp Stem Cells and Antibacterial Effect - Albashari, Abdullkhaleg Ali; He, Yan; Albaadani, Mohammed A.; Xiang, Yangfan; Ali, Jihea; Hu, Fengting; Zhang, Yuan; Zhang, Keke; Luo, Lihua; Wang, Jianming; Ye, Qingsong (Frontiers in Cell and Developmental Biology, 2021)
Titanium modifications with different silver loading methods demonstrate excellent antibacterial properties. Yet, pure silver nanoparticles with limited bioactive properties may delay bone regeneration surround the dental implant. Therefore, loading silver with bioactive drugs on titanium surfaces seems to be a very promising strategy. Herein, we designed a silver (Ag) step-by-step cross-linked with the fibroblast growth factor (bFGF) by polydopamine (PDA) and heparin on titanium nanotube (TNT) as its cargo (TNT/PDA/Ag/bFGF) to improve the implant surface. Our results showed that TNT/PDA/Ag/bFGF significantly enhanced the osteogenic differentiation of dental pulp stem cells (DPSCs). It also showed an excellent effect in bacterial inhibition and a reduction of pro-inflammatory factors through inhibition of M1 macrophage activity. These results showed that basic fibroblast growth factor (bFGF) cross-linked silver coating on titanium nanotubes presented good osteogenic differentiation, early anti-inﬂammatory, and antibacterial properties. Together, this novel design on titanium provides a promising therapeutic for dental implants.